1993
DOI: 10.1080/10447319309526071
|View full text |Cite
|
Sign up to set email alerts
|

Visual comfort in using different VDT screens

Abstract: In order to meet the goal of user comfort of information displays, visual problems of video display terminal (VDT) work were studied through the analysis of visual functions in two experiments. Eye movement analysis, in Experiment 1, revealed that VDT operators had to move their eyes 2.5 times faster than traditional clerical workers. Lens accommodation, pupil size, and subjective visual comfort were investigated in Experiment 2. A significant correlation was found between the velocity of lens accommodation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 4 publications
3
28
2
1
Order By: Relevance
“…TFT-LCD offers superior visual performance to CRT [13]. On the other hand, Saito et al [8] and Hollands et al [15] reported that working with an LCD screen may be less comfortable than CRT, and moreover, it was associated with longer response times. These contradictory results demonstrated that the influence of screen type on visual fatigue and performance remains uncertain.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…TFT-LCD offers superior visual performance to CRT [13]. On the other hand, Saito et al [8] and Hollands et al [15] reported that working with an LCD screen may be less comfortable than CRT, and moreover, it was associated with longer response times. These contradictory results demonstrated that the influence of screen type on visual fatigue and performance remains uncertain.…”
Section: Introductionmentioning
confidence: 97%
“…and environmentbased factors (such as close viewing distance, low luminance contrast, etc.). VDT operators typically have to move their eyes faster than clerical workers performing traditional work tasks, such as reading and writing without VDTs [8]. The high density office work created by the introduction of VDTs may cause VDT-related complaints [9].…”
Section: Introductionmentioning
confidence: 99%
“…Displays and keyboards, whose optical and physical characteristics are totally different from those of paper and pencil, caused a sharp increase in the number of users experiencing eye fatigue, pain or dryness, shoulder stiffness, and back and low back pain. Among the many subsequent surveys and experimental studies, Saito observed that when working at a computer one's posture tends to become more tightly restrained and eye movement busier than when writing with "pencil and paper" 1) , Sotoyama noted that the ocular surface area, the surface area of the eyeball which exposed to the air, increases due to upward gaze 2) , and Abe pointed out a decrease in tears during upward gaze 3) all referred to as among causative factors in shoulder stiffness or eye pains.…”
Section: Introductionmentioning
confidence: 99%
“…La plupart des articles [14,15] recommandent un fond blanc (meilleur contraste) et des caractères noirs, mais cela pour des personnes ayant une bonne acuité visuelle. Les personnes âgées ayant pour la plupart des déficits visuels, le fond blanc n'est pas adapté.…”
Section: Couleur De Fond D'écran Et Contraste De Luminanceunclassified